Three dimensional characterization and multi-scale modelling of damage in natural biomaterials - Yan, L; Mora, L; Boughton, O; Abel, R; Marrow, T (International Congress on Fracture, 2017)
The deformation and fracture behaviour of examples of natural biomaterials (Common limpet and cortical bone) has been investigated using in-situ mechanical tests observed by X-ray computed tomography. The 3-D displacement field within the deformed specimens has been measured by digital volume correlation of tomographs. These data have then been used to extract the stress/strain properties and failure criteria of the biomaterials via cohesive finite element models into which the displacement field provides the 3-D boundary conditions.